2022
DOI: 10.1186/s40945-021-00124-z
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapists perceived role in managing anxiety in patients with relapsing-remitting multiple sclerosis: a mixed-methods study

Abstract: Background Anxiety is common for people with Multiple Sclerosis (PwMS) and is higher in those with relapsing-remitting MS (RRMS) and in community-based samples. Anxiety can impact self-efficacy, pain, fatigue, engagement in physical activity and treatment adherence, all of which influence the rehabilitation process. Little is known about how physiotherapists manage anxiety in PwMS and the challenges associated with anxiety throughout the rehabilitation process, in community and outpatient setti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
0
0
Order By: Relevance
“…Similarly, the results of Hooblau et al’s 17 study mirror our findings, demonstrating that public sector physiotherapists in KwaZulu-Natal exhibited good attitudes towards managing people living with mental illness and mental health. Moreover, and aligning with our findings, Lucas and Parker’s 27 results showed that in outpatient and community rehabilitation settings, physiotherapists dealt with anxiety in patients with multiple sclerosis and believed they could help when it manifested.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similarly, the results of Hooblau et al’s 17 study mirror our findings, demonstrating that public sector physiotherapists in KwaZulu-Natal exhibited good attitudes towards managing people living with mental illness and mental health. Moreover, and aligning with our findings, Lucas and Parker’s 27 results showed that in outpatient and community rehabilitation settings, physiotherapists dealt with anxiety in patients with multiple sclerosis and believed they could help when it manifested.…”
Section: Discussionsupporting
confidence: 90%
“…Dandridge et al 29 conducted a survey of physiotherapy students’ experiences and attitudes toward treating individuals with mental illness and found that students felt that they needed more education and training in this area. Similarly, Lucas and Parker 27 conducted a mixed-methods study on the perceived role of physiotherapists in managing anxiety in patients with relapsing-remitting multiple sclerosis and found that physiotherapists’ perceived role in managing anxiety was limited due to a lack of training and experience. The findings of the current study are consistent with those of these previous studies and highlight the need for more emphasis on the education and training of healthcare professionals, including physiotherapists, in managing the physical health problems of patients with mental illness.…”
Section: Discussionmentioning
confidence: 99%